Corneal Astigmatism Alteration after Combined Silicone Oil Removal and Cataract Surgery with Intraocular Lens Implantation - Zhenyu Ji; Ting Su; Lu Li; Tao He; Yu Su (Journal of Ophthalmology)
Purpose. To explore short-term changes in corneal astigmatism after combined silicone oil removal and cataract (SORC) surgery. Methods. We enrolled 89 patients (43 men and 46 women). Zeiss IOLMaster was used to measure corneal astigmatism status and axial length on the day before and after the SORC surgery. Best-corrected visual acuity (BCVA) and intraocular pressure (IOP) were recorded. The results were compared to the outcomes at 3 days, 1 week, and 1 month postoperatively. Results. Compared to baseline, K1 decreased significantly at 3 days postoperatively (P=0.016), 1 week (P=0.009), and 1 month (P=0.035), while K2 increased significantly at 3 days postoperatively (P = 0.002), 1 week (P < 0.001), and 1 month (P = 0.001), as well as corneal astigmatism (all P < 0.001). Compared to that at the baseline, BCVA significantly improved at 3 days, 1 week, and 1 month postoperatively (all P<0.001). Meanwhile, IOP decreased significantly at 3 days postoperatively (P<0.001), 1 week (P=0.005), and 1 month (P=0.007). Similarly, axial length decreased at all follow-up time points (all P<0.001). Conclusion. Corneal astigmatism increased in the short term after the SORC operation but gradually decreased at 1 month postoperatively. BCVA improved steadily, and SORC was widely used in the clinic.